5 - The Social Sciences at the Crossroads: Challenges and Opportunities at Addis Ababa University - Abeje Berhanu (Journal of Higher Education in Africa, 2014)
The social sciences are at the crossroads in Ethiopia. This is because go- vernment’s overt policy favours the scientific and engineering disciplines and this translates to allocating more money to them. This could lead to acute shortage of research funding for MA and PhD programmes in the social sciences and lack of investment in infrastructure, resulting in shortage of office space for staff and shortage of classrooms and offices for PhD students. In the long run, this could lead to much lower support for staff development with fewer and fewer students choosing social science fields. But the social sciences can convert these challenges into opportunities. One way of doing this is to emphasize quality education – this being the key issue identified in recent debates on the nature and direction of higher education in Ethiopia. The saying ‘small is beautiful’, which in this case can be stated, ‘small is viable’, is applicable to the future of the social sciences in the Ethiopian higher education system. A manageable student size, both at the undergraduate and graduate level, can help the social sciences to provide relevant and quality education for their students.